Reevaluating the placebo effect in medical practice - Colloca, Luana (2014)
Recent findings on placebo research corroborate the evidence that the placebo effect represents a promising model to shed new light on the brain-mind-body interactions. In particular, this research has partially elucidated the role of how patients’ expectations and the quality of physician-patient communication can influence the efficacy of interventions and overall clinical outcomes. Accordingly, the study of the placebo effect should be incorporated in the core clinical practice curriculum of all health practitioners. While the growing knowledge of the placebo effect points to it as an irreducible primary reality of the medical sciences, an ethical analysis aimed at avoiding the misuse of placebos is needed, while maximizing the opportunity for beneficial placebo effects.